Análise de indicadores de gestão e desempenho acadêmico: um estudo de caso dos cursos de graduação do campus da Universidade Federal do Ceará no Cariri - Araújo, Francisco Ildisvan de (2013)
This paper presents the process and results of scientific research developed from analysis of management indicators and academic performance of undergraduate courses in Campus of the Federal University of Ceará ( UFC ) in Cariri , between the years 2007 and 2011 . The research is part of an initial theoretical basis on topics such as teaching evaluation Top Brazilian, management indicators and academic performance and strategic management Higher Education Institutions ( HEIs ) . The main objective was to develop a set of exploratory analyzes with qualitative and qualitative and descriptive approach of the series basic historical data and results of some indicators of management adopted by Court of Audit ( TCU ) and internal indicators of academic performance UFC explored individually in the set size of the undergraduate Campus Cariri . So we started with the organization - and partialization for academic unit study - the basic data components and the results of these indicators , presented a consolidated basis , the size of the entire university, in one of the most important institutional sources of information : the Statistical Yearbook of the UFC . Another goal achieved the work was to develop a finite set of qualitative and quantitative analysis , seeking explore possible relationships between the Success Rates of Graduate ( TSCG ) with the results of other indicators of performance management and the academic unit searched. Among the important results and conclusions of the work , considering the relevance to the strategic management of the institution and the academic unit studied, highlight the diagnoses resulting series of evaluative analysis of the basic data and indicators of academic performance ; implications identified and suggested applications in terms of threats and opportunities for performance improvement and Cariri Campus , consequently the UFC , measurements in these indicators . Another highlight is the potential use this information as input for decision making for the improvement of quality of academic activities on the campus of the UFC Cariri , especially when considered the prospect has already taken place , this academic unit give rise to new UFCA ( Federal University of Cariri ) .